LEGAL PROTECTION FOR CHILDREN AS PERPETRATORS OF TERRORISM CRIMINAL ACTS - Sitinjak, Humala; Damanik, Jenriswandi; Simarmata, Indra Christoper; Ginting, Natalia; Gaol, Yesmita Lumban (Inspiring Law Journal, 2025)
Legal protection for children who are exploited by adults involved in acts of terrorism is subject to the provisions of Law Number 11 of 2012 concerning the Juvenile Justice System which regulates that children as perpetrators of criminal acts can be subject to diversion as an effort of restorative justice. In the provisions of Article 6 of Law Number 11 of 2012, it states that diversion aims to achieve peace between victims and children as a manifestation of efforts to resolve children's cases outside the judicial process. The purpose of the diversion mechanism is to prevent children from deprivation of liberty and encourage the community to participate and instill a sense of responsibility in children and as a form of protection for the future of children who are exploited by adults to commit acts of terrorism in particular. As regulated in Article 7 of Law Number 11 of 2012 which states that cases of children who commit criminal acts that can be diverted are criminal acts with a prison sentence of less than 7 years and not a repetition of the crime. Article 9 of Law Number 11 of 2012 emphasizes that the lower the criminal threat, the higher the priority for diversion. Children who are perpetrators of terrorism crimes are victims of crimes and not perpetrators of crimes because they are victims who are exploited by adults who should receive protection, so children who are involved in terrorism crimes should receive rehabilitation